Technique utilisation and efficiency in competitive Brazilian Jiu-Jitsu matches at white and blue belts. (4th May 2019) - Williams, Jonathan; Callaway, Andrew; Gara, Mike; Tattersall, Paris
ABSTRACT: Despite its increasing popularity, little is known about Brazilian Jiu-Jitsu and what makes a successful fighter. This work aims to start answering questions about the most used and successful techniques to allow development of coaching methods towards enhancing performance at lower belt levels. One-hundred and forty tournament fights were analysed. The most common takedown was guardpull with 94% success. Significantly more single leg takedowns were attempted for blue belts (BBs), compared to white belts (WBs) ( p = 0.013). However, there was no significant difference in success ( p = 0.150). WBs used three main guardpasses with 93% covering knee slice, knee pin and bullfighter. A greater variety of passes were witnessed at BB with 71% coming from these three passes. The four most commonly attempted guard sweeps were scissor sweep, back take, Xguard sweep and SitUp sweep all experiencing varying levels of success: 55% for the scissor sweep, 60% back take, 63% Xguard sweep and 38% for the sit up sweep. Of all the submissions attempted 34% were for arm bar, 21% triangle, 12% cross collar choke but there were almost an inverse relationship between use and success with the least used having higher success rates, demonstrating that variety in submissions could lead to greater chances of success.